Research on the Application Decision Making of Information Technology in the Sustainable Supply Chain of Cross-Border E-Commerce - Feng Ding; Jiazhen Huo (Applied System Innovation, 2025)
Cross-border e-commerce (CBEC) is rapidly growing as a global trade engine. Simultaneously, its rapid expansion also poses environmental challenges and worsens supply chain sustainability. Advanced information technology (IT) significantly enhances supply chain visibility and promotes cooperation, thereby improving the efficiency and sustainability of CBEC supply chains. However, the application of IT is accompanied by an increase in service costs, necessitating a comprehensive balance for enterprises. This paper constructs a CBEC supply chain consisting of an overseas supplier and two merchants, where one merchant adopts advanced IT to provide differentiated services. A game-theoretic model is employed to analyze the IT application decisions under price and service competition in supply chain members’ cooperative and non-cooperative scenarios. The results indicate that service differentiation generated by advanced IT is influenced by consumer preferences. Merely applying advanced IT may not necessarily improve competitiveness and efficiency, and may even lead to negative utility. When the products sold are similar and the service cost coefficient is constant, those who apply advanced IT to provide higher service levels can gain competitive advantages and obtain more profits. When the service differentiation between merchants is constant, CBEC supply chains implementing centralized strategies can achieve greater profits.